Dehydroepiandrosterone reduces expression of glycolytic and gluconeogenic enzymes in the liver of male and female rats - Mayer, Doris; Reuter, S.; Hoffmann, Herbert; Bocker, Thomas; Bannasch, Peter (International journal of oncology, 1996)
The in vivo effect of dehydroepiandrosterone (DHEA) on hepatic glycogen content and on glucose metabolizing enzymes was investigated in male and female Sprague-Dawley rats treated with 0.6% (w/w) DHEA in the diet for 3, 7, 14, 28 and 140 days. The glycolytic enzymes studied (glucokinase, hexokinase, pyruvate kinase) showed a significant persistent decrease in activity in both sexes after 3-7 days of treatment. Gluconeogenic enzymes (glucose-6-phosphatase, fructose-1,6-bisphosphatase) were increased after 3 days, but decreased after 7-14 days. Glycolytic enzymes showed a stronger reduction than gluconeogenic enzymes. Females were slightly more affected than males. Glucose-6-phosphate dehydrogenase was unchanged in females, but increased in males. Glycogen content and the activity of glycogen phosphorylase were reduced after 3 days of treatment. mRNA analysis of glucokinase and phosphorylase indicated that these enzyme alterations were accompanied by reduced transcriptional expression, while glucose-6-phosphate dehydrogenase mRNA levels were unchanged. Withdrawal of DHEA from 4 week-treated rats was associated with an almost complete reversibility of the enzyme alterations after 2 weeks. After long-term treatment (140 days) glucokinase, glucose-6-phosphatase and fructose-1,6-bisphosphatase activities were no longer altered. Since DHEA treatment affects the key enzymes of glucose metabolic pathways in the same sense, it is suggested that DHEA does not regulate individual enzymes but rather common regulatory factors or signalling pathways.
Gesehen am 06.12.2023